Endoscopic ultrasound-elastography (strain ratio) in the diagnosis of solid pancreatic lesions: A prospective cohort study - Carrara, Silvia (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Endoscopic ultrasound (EUS) elastography is a noninvasive ultrasound technique that measures the stiffness of tissues. Both a qualitative score and a quantitative method (strain ratio [SR]) can be used to study the hardness of solid pancreatic lesions (SPLs). This single-center prospective cohort study aimed to evaluate the efficacy of the combination of EUS elastography and SR for the diagnosis of SPL using the elastography software on the new Olympus echo-processor EU-ME2. METHODS: Two different areas were selected: area A included the tumor; area B was placed in a soft peri-tumoral normal (parenchymal SR [pSR]) and in the gastrointestinal wall (wall SR [wSR]). The quantitative score of elastography was calculated by the SR method (area B/area A). Elasticity measurements were performed 3 times in each procedure. Means of pSR and of wSR were calculated and used as final results for each patient. Final diagnosis was made on the basis of EUS-guided fine needle aspiration, surgical specimens, or follow-up of at least 6 months. RESULTS: Study population included 100 patients and a total of 102 SPLs. Mean lesion (standard deviation) size was 27.1 mm (12.4). The final diagnosis classified SPL into adenocarcinoma (ADC, n = 69) or benign lesions (n = 33). Benign lesion group included 19 neuroendocrine tumors. ROC analysis identified a cutoff of SR of 9.1 as the best value for the detection of malignancy. Sensitivity, Specificity, positive predictive value, negative predictive value, and accuracy with their cutoff value for malignancy are shown in the full article. Univariate logistic regression analysis showed that both pSR and wSR were significant discriminators for ADC and benign SPL. The overall area under the characteristic curve was 88.6% (81.2%–96.0%), indicating good ability in discriminating between cancers and benign lesions. The major limitation of this study is the low number of benign masses, but these preliminary data showed the feasibility of the SR calculated with the Olympus EU-ME2 echo-processor and the higher SR values in ADC. CONCLUSIONS: EUS-elastography may be helpful in the diagnosis of SPLs, especially in the identification of those suspected for ADC. Further studies are needed to assess its diagnostic accuracy and reproducibility.